Bioactive diterpenoids and sesquiterpenoids with different skeletons from Salvia digitaloides Diels. (January 2023) - Liu, Xu; Zhan, Xiao-Qing; Wang, Mei-Jie; Cui, Wen-Bo; Chen, Xiao-Han; Qi, Feng-Ming; Yu, Jian-Ning; Dai, Jian-Ye; Fei, Dong-Qing; Zhang, Zhan-Xin
Abstract: Salvia has been regarded as a beneficial healing herb in ancient Egypt, Rome and Greece, and is listed as an official medicine in the pharmacopoeias of many countries worldwide. Currently, Salvia is widely used to flavor and preserve food. Here, two undescribed norabietane-type diterpenoids, sadigitaloides A and B, two undescribed germacrane-type sesquiterpenoids, sadigitaloides C and D, five undescribed guaiane-type sesquiterpenoid lactones, sadigitaloides E-I, two undescribed noreudesmane-type sesquiterpenoids, sadigitaloides J and K, one known diterpenoid, three known sesquiterpenoids, and three other types of known compounds were isolated from the 95% ethanol extract of the whole plants of Salvia digitaloides . Their structures and absolute configurations were characterized using 1D and 2D NMR spectroscopic techniques, electronic circular dichroism (ECD) calculations, HRESIMS experiments, and single-crystal X-ray diffraction analysis. Some compounds were evaluated for their anti-inflammatory activities against lipopolysaccharide (LPS)-induced TNF-α production in rat macrophage NR8383 cells. Sadigitaloide A showed noticeable anti-inflammatory activity at a concentration of 100.0 μM. At a concentration of 60 μM, sadigitaloide B exhibited better protection of dopaminergic neurons than the positive control n-butylidenephthalide in the Caenorhabditis elegans model injured by 6-OHDA. The phytotoxic activities of some compounds were attributed to considerable inhibitory effects on the growth of the roots and hypocotyls of Raphanus sativus L seedlings, especially cis, trans -abscisic acid, whose inhibition rates were much higher than those of glyphosate at concentrations ranging from 50 to 400 ppm. These results indicated that abietane-type diterpenoids possessed excellent anti-inflammatory and neuroprotective activities and further suggested that the low-molecular-weight compounds exhibited outstanding phytotoxic activities. Graphical abstract: Image 1 Highlights: Eleven unreported terpenoids were isolated from Salvia digitaloides. Three sesquiterpenoid skeleton types were isolated for the first time from Salvia digitaloides. Sadigitaloide A significantly inhibited the generation of the proinflammatory cytokine TNF-α. Sadigitaloide B exerted a significant protective effect on 6-OHDA injury in dopaminergic neurons. Some compounds showed considerable phytotoxic activity.